Management of surgery, menorrhagia and child-birth for patients with unclassified bleeding disorders: a systematic review of cohort studies. Issue 6 (September 2021) - Desborough, Michael J.R.; Obaji, Samya; Lowe, Gillian C.; Doree, Carolyn; Thomas, Will
Abstract : N/A: Unclassified bleeding disorders account for 2.6% of all new bleeding disorder registrations in the UK. The management of the bleeding phenotype associated with these disorders is poorly described. Systematic review and meta-analysis to determine the bleeding rates associated with tranexamic acid, desmopressin, platelet transfusion, plasma transfusion and recombinant activated factor VII, for patients with unclassified bleeding disorders undergoing surgery, childbirth or with menorrhagia. We searched for randomized controlled trials in MEDLINE, Embase, The Cochrane Central Register of Controlled Trials, PubMed, ISI Web of Science and the Transfusion Evidence Library from inception to 24 February 2020. Wherever appropriate, data were pooled using the metaprop function of STATA. Two studies with 157 participants with unclassified bleeding disorders were identified. The pooled risk of minor bleeding for patients undergoing surgery treated with peri-operative tranexamic acid was 11% (95% confidence interval 3–20%; n = 52; I 2 = 0%); the risk for desmopressin and tranexamic acid in combination was 3% (95% confidence interval 0–7%; n = 71; I 2 = 0%). There were no instances of major bleeding. In one procedure, 1 of 71 (1.4%), treated with a combination of desmopressin and tranexamic acid, the patient had a line-related deep vein thrombosis. There were too few patients treated to prevent postpartum haemorrhage or for menorrhagia to draw conclusions. The GRADE quality of evidence was very low suggesting considerable uncertainty over the results. However, both tranexamic acid, and the combination of tranexamic and desmopressin have high rates of haemostatic efficacy and have few adverse events. Protocol registration: PROSPERO CRD42020169727. Abstract : Supplemental Digital Content is available in the text